A novel C-type lectin LvCTL 4.2 has antibacterial activity but facilitates WSSV infection in shrimp (L. vannamei). (January 2022) - Huang, Yu-Hsun; Kumar, Ramya; Liu, Chun-Hung; Lin, Shih-Shun; Wang, Han-Ching
Abstract: Glycan-binding protein C-type lectin (CTL), one of the pattern recognition receptors (PRRs), binds to carbohydrates on the surface of pathogens and elicits antimicrobial responses in shrimp innate immunity. The objective was to identify and characterize a novel C-type lectin LvCTL 4.2 in Litopenaeus vannamei . The LvCTL 4.2 protein consisted of a signal peptide at the N terminal and a carbohydrate-recognition domain (CRD) with a mutated mannose-binding (Glu-Pro-Ala; EPA) motif at the C terminal, and thereby has a putative secreted mannose-binding C-type lectin architecture. LvCTL 4.2 was highly expressed in nervous tissue and stomach. Infection with white spot syndrome virus (WSSV) induced expression of LvCTL 4.2 in shrimp stomach at 12 h post infection. Conversely, there was no obvious upregulation in expression of LvCTL 4.2 in stomach or hepatopancreas of shrimp with AHPND (acute hepatopancreas necrosis disease). Pathogen binding assays confirmed recombinant LvCTL 4.2 protein (rLvCTL 4.2) had significant binding ability with the WSSV virion, Gram-negative, and Gram-positive bacteria. Moreover, rLvCTL 4.2 had strong growth inhibition of Vibrio parahaemolyticus . Silencing LvCTL 4.2 suppressed WSSV replication, whereas pretreatment of WSSV with rLvCTL 4.2 facilitated viral replication in vivo . In conclusion, LvCTL 4.2 acted as a PRR that inhibited AHPND-causing bacteria, but facilitated WSSV pathogenesis. Highlights: A novel C-type lectin LvCTL 4.2 was identified from white shrimp ( Litopenaeus vannamei ). rLvCTL 4.2 had significant binding ability with the WSSV virion, Gram-negative, and Gram-positive bacteria. rLvCTL 4.2 had strong growth inhibition of Vibrio parahaemolyticus. Silencing LvCTL 4.2 suppressed WSSV replication. WSSV genome copy numbers were increased when shrimp were challenged with WSSV pretreated with rLvCTL 4.2.